EU-China Relationships as the Outcome of Discrepancy between Them - Szuster, Mariusz (Relacje między UE a Chinami jako efekt rozbieżności między nimi, 2010)
Relationships between UE and China concern many fields. Except for economics discrepancy, important differences are connected with human rights, climate protection and policy of China as a prospective world power. Many arguments prove that future relations may be dominated by this country.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 349-356
Keywords: international trade; economic policy